Experimental study on severe slugging mitigation by applying wavy pipes - Xing, Lanchang; Yeung, Hoi; Shen, Joseph; Cao, Yi (Elsevier, 2013)
Wavy pipes were installed in the pipeline for mitigating severe slugging in pipeline/riser systems. Experimental results have revealed that: with a wavy pipe applied, the operating region of severe slugging is reduced; the severity of severe slugging and oscillation flow is mitigated; the wavy pipe performs better with its outlet located upstream of the riser base. The wavy pipe is essentially reducing the slug length. For severe slugging the wavy pipe works by accelerating the movement of the gas in the pipeline to the riser base; for the oscillation flow it works by mixing the gas/liquid two phases.